Practice framework theorizing in correctional rehabilitation: Lessons from constitutive penology - Arrigo, Bruce A. (Legal and criminological psychology, 2024)
This paper applies key insights from constitutive penology to advance the practice framework literature in correctional rehabilitation. First, I provide some brief commentary on the origins and subsequent development of constitutive thought in studies of governance, crime and justice. Second, I outline the central ontological convictions and epistemological commitments of constitutive penology. Third, I explain where and how the ontic and epistemic ‘lessons’ of constitutive penology contribute to the conversation about practice framework theory and therapeutic practice in correctional rehabilitation. These comments especially emphasize the importance of (a) rethinking the responsibility of theory in therapeutic practice; (b) reframing the method of study in the practice of therapy and (c) repurposing the practice guidelines for undertaking therapeutic work.